2021
DOI: 10.1002/path.5662
|View full text |Cite
|
Sign up to set email alerts
|

Independent real‐world application of a clinical‐grade automated prostate cancer detection system

Abstract: Artificial intelligence (AI)-based systems applied to histopathology whole-slide images have the potential to improve patient care through mitigation of challenges posed by diagnostic variability, histopathology caseload, and shortage of pathologists. We sought to define the performance of an AI-based automated prostate cancer detection system, Paige Prostate, when applied to independent real-world data. The algorithm was employed to classify slides into two categories: benign (no further review needed) or sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 18 publications
1
56
0
Order By: Relevance
“…Indeed, a recent study found that application of IA in real-world clinical practice reduced diagnostic time by 65%. 25 Likewise, Hossain and colleagues reported that the application of the LD IA for HER2 DISH also reduced diagnostic time, from 3 to 20 min per manual score compared with 1 min for the algorithm to quantify the HER2/Chr17 ratio after pathologist annotation. 24 Thus, it will be critical for future studies to address the value of the uPath HER2 DISH IA in increasing workflow efficiencies, as demonstrating reduction of diagnostic interpretation time has substantial value for both the patient and oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent study found that application of IA in real-world clinical practice reduced diagnostic time by 65%. 25 Likewise, Hossain and colleagues reported that the application of the LD IA for HER2 DISH also reduced diagnostic time, from 3 to 20 min per manual score compared with 1 min for the algorithm to quantify the HER2/Chr17 ratio after pathologist annotation. 24 Thus, it will be critical for future studies to address the value of the uPath HER2 DISH IA in increasing workflow efficiencies, as demonstrating reduction of diagnostic interpretation time has substantial value for both the patient and oncologist.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, there is an unmet opportunity for artificial intelligence-driven efforts to use anti-PSMA IHC for refining algorithms used for detecting suspicious regions in treated prostate tumors, as PSMA demonstrates superior specificity for tumor than many IHC markers. 23–25 Current diagnostic efforts continue to be plagued by atypical histologies requiring additional expert pathological review, with these tumors more likely to be misclassified by automated systems or without specialized immunostains. 18,26 In the current study, we showed that anti-PSMA IHC alone had 97% sensitivity and 82% specificity for detecting residual disease when each ROI was separately examined by an expert prostate pathologist using H&E and other confirmatory stains.…”
Section: Discussionmentioning
confidence: 99%
“…The Paige Prostate ® system, successor to prototypal version Paige Prostate Alpha ® , was subject to extensive multinational validation spanning ≥150 different institutions and a diversity of clinical and demographic characteristics from ≥7000 patients including differing tumor sizes, grades, and patient ethnicities [ 23 , 83 , 84 , 85 , 86 , 87 ]. The system achieved a sensitivity of 97.7% and a specificity of 99.3% in detecting cancer in 1876 prostate CNB WSIs, also demonstrating 99% sensitivity and 93% specificity at part-specimen level while upgrading pathologist-ascribed benign/suspicious patient diagnosis to malignant after identification [ 84 , 85 ].…”
Section: Actuating Clinical Implementation Through Achieving Generali...mentioning
confidence: 99%